Pterobryopsis siheiana (Bryophyta: Pterobryaceae)—a new species from the Western Ghats of India - Daniels, A.e.d.; Athira, S.; Kuznetsova, O.i.; Ignatov, M.s. (Phytotaxa, 2024)
Pterobryopsis siheiana A.E.D. Daniels & S. Athira is described as a new species from the southern part of the Western Ghats. It differs from other congeners in a combination of a large group of quadrate to subquadrate supra-alar cells above the reddish-brown tinted alar cells in both stem and branch leaves, the variable costae between stem and branch leaves, and the apical cells strongly differentiated between stem and branch leaves. The ITS sequence data support the separate position of P. siheiana and indicate its closest relationship with P. schmidii and P. divergens.